2007
DOI: 10.1108/09649420710761446
|View full text |Cite
|
Sign up to set email alerts
|

Career success and satisfaction: a comparative study in nine countries

Abstract: PurposeThis project aims to examine levels of career and life satisfaction among successful women in nine countries in the Americas.Design/methodology/approachA structured survey and in‐depth interviews were used, and a variety of occupations, demographics, and personality characteristics assessed – 1,146 successful women from nine countries in the USA responded the survey: 105 from Argentina, 210 from Brazil, 199 from Canada, 84 from Chile, 232 from Mexico, 126 from the USA, and 190 from three countries in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
1
17
1
2
Order By: Relevance
“…Age has been shown in some studies to have a curvilinear relationship; the older employees being more satisfied than the younger ones (Punnett et al, 2007). In a study conducted in Australia by Dua (1994), younger staff reported more job stress than older staff.…”
Section: Possible Causes Of Stress In Higher Educationmentioning
confidence: 98%
See 1 more Smart Citation
“…Age has been shown in some studies to have a curvilinear relationship; the older employees being more satisfied than the younger ones (Punnett et al, 2007). In a study conducted in Australia by Dua (1994), younger staff reported more job stress than older staff.…”
Section: Possible Causes Of Stress In Higher Educationmentioning
confidence: 98%
“…The deficit of job control in females, however, increased towards less qualified occupations. Job strain was less prevalent in men than in women, without apparent regional heterogeneity (de Smet et al, 2005).Age has been shown in some studies to have a curvilinear relationship; the older employees being more satisfied than the younger ones (Punnett et al, 2007). In a study conducted in Australia by Dua (1994), younger staff reported more job stress than older staff.…”
mentioning
confidence: 93%
“…In a study of careers of women which conducted by Punnett et al (2007) showed that career satisfaction is influenced by career success. Ballout's (2009) study revealed that, career commitment has a significant influence of career satisfaction through the moderation effect of self efficacy.…”
Section: The Relations Among Career Commitment Career Satisfaction mentioning
confidence: 99%
“…A recent comparative study of nine countries found no differences in career success based on occupation or country and most demographic variables (Punnett, et al, 2007). In accord with this previous work, Noordin.et al (2002) also found no significant differences between the two groups with regard to career identity and career www.ccsenet.org/ijbm International Journal of Business and Management Vol.…”
Section: H2: There Were 12 Main Predictors Of Career Success They Armentioning
confidence: 54%